Fruit shape loci sun, ovate, fs8.1 and their interactions affect seed size and shape in tomato - Chen, Jie; Pan, Bingqing; Li, Zixiong; Xu, Yue; Cao, Xiaomeng; Jia, Jingjing; Shen, Huolin; Sun, Liang (Frontiers in Plant Science, 2023)
Seed size and shape are not only critical for plant reproduction and dispersal, but also important agronomic traits. Tomato fruit shape loci sun, ovate and fs8.1 regulate the morphology of fruit, flower, leaf and stem, and recently their functions in seed morphogenesis have also been noticed. However, mechanism underlying seed morphology variation has not been systematically investigated yet. Thus, using the near isogenic lines (NILs) harboring one, two or three of the fruit shape loci, histological, physiological and transcriptional bases of seed morphology change have been studied. sun and ovate showed potential abilities in decreasing seed size, whereas, fs8.1 had a potential ability in increasing this parameter. Interactions between two loci and the interaction among three loci all led to significant decrease of seed size. All the loci significantly down-regulated seed shape index (SSI), except for sun/fs8.1 double NIL, which resulted in the reductions in both seed length and width and finally led to a decreased trend of SSI. Histologically, seed morphological changes were mainly attributed to the cell number variations. Transcriptional and physiological analyses discovered that phytohormone-, cytoskeleton- as well as sugar transportation- and degradation-related genes involved in the regulation of seed morphology by the fruit shape loci.